Decision-making about clinical trial options among older patients with metastatic cancer who have exhausted standard therapies. Issue 5 (June 2022) - Tsang, Mazie; DeBoer, Rebecca J.; Garrett, Sarah B.; Dohan, Daniel
Abstract: Objectives: Older adults under-enroll in early phase cancer clinical trials. There are limited data on their trial experiences, which hampers our ability to understand potential reasons and responses to under-enrollment. We aimed to explore older adults' experiences and deliberations with phase 1 trials. Materials and Methods: We analyzed 101 in-depth interviews with 39 adults (average 2.6 interviews per participant) about their experiences with phase 1 trials. All respondents were ≥ 65 years and had advanced cancer. Interviews lasted 60–90 min and were audio-recorded, transcribed, and analyzed to identify respondents' understanding of clinical research, perceptions of early phase trials, and experiences with enrollment. Results: Clinical trial participation was an interactive process that unfolded over time. Older adults relied on ongoing guidance and discussion with their oncologist to navigate the process. Respondents were generally interested in life-prolonging therapies, including enrollment in early phase clinical trials, but did not necessarily state this explicitly to their oncologist. While respondents did not mention age as a limitation to trials participation, participants age > 70 were less enthusiastic about participation and more often discussed their quality of life and weighed benefits of trial participation in the context of their remaining months of life. Conclusion: Early phase clinical trial enrollment is complex, and older adults rely on their oncologist to navigate this process. Acknowledging this complexity through shared decision-making may ensure that older adults have appropriate opportunities to enroll in early phase clinical trials and guard against inappropriate under-enrollment.